2018
DOI: 10.1155/2018/3645386
|View full text |Cite
|
Sign up to set email alerts
|

Placental Ras Regulates Inflammation Associated with Maternal Obesity

Abstract: Heightened placental inflammation and dysfunction are commonly associated in pregnant obese women compared to their pregnant lean counterparts. The small GTPase superfamily members known as the rat sarcoma viral oncogene homolog (Ras) proteins, in particular, the K-Ras and H-Ras isoforms, have been implicated to regulate inflammation. The aims were to determine the placental Ras expression and activity with maternal obesity and its role in regulating placental inflammation. Human placenta was obtained at term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Pathologic examination of the placenta in the HIE cases could have added interesting information, in particular on the pathophysiological mechanisms leading to HIE. High maternal BMI and smoking during pregnancy can indeed be associated with placental dysfunction and particularly endothelial dysfunction (22) (23), and this dysfunction could lead to chronic hypoxemia, and impair neurological neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic examination of the placenta in the HIE cases could have added interesting information, in particular on the pathophysiological mechanisms leading to HIE. High maternal BMI and smoking during pregnancy can indeed be associated with placental dysfunction and particularly endothelial dysfunction (22) (23), and this dysfunction could lead to chronic hypoxemia, and impair neurological neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine profile is driven by several inflammatory pathways, including the activation of receptors for advanced glycation end-products (RAGEs) by AGEs [61] and activation of Toll-like receptor 4 (TLR4) by NEFAs [60]. In turn, these pathways promote nuclear factor kappa light chain enhancer of activated B cells (NF-κB), the c-Jun N-terminal kinase (JNK), and rat sarcoma virus (Ras) signaling, leading to increased generation of reactive oxygen species (ROS) and the secretion of proinflammatory cytokines such as IL-6, IL-8, MCP-1, tumor necrosis factor α (TNF-α), and IL-1β [62]. Interestingly, a randomized double-blind controlled trial showed that ω3 supplementation in early obese pregnancy prevented the obesityassociated increase in TLR4 signaling and led to a shift in the cytokine profile, indicating that PUFAs are beneficial for healthy placental function [63].…”
Section: Cytokine Profilementioning
confidence: 99%
“…Although levels of both the saturated fatty acid palmitate and the monounsaturated fatty acid oleate are elevated in obese pregnant women [113], only exposure to palmitate facilitated the development of ER stress in the syncytiotrophoblast, driving translocation of ATF4 and downstream apoptosis mediated by C/EBP homologous protein (CHOP). Furthermore, increased placental palmitate content drives a potent inflammatory response in the obese placenta, including activation of the inflammasome and secretion of inflammatory cytokines [62,114]. This inflammatory response is likely to form a reciprocal cause-and-effect relationship with placental ER stress [91,104,115,116].…”
Section: Trends In Molecular Medicinementioning
confidence: 99%
“…Also, trophoblast cells such as CTB, STB, and EVT encode for a Receptor Tyrosine Kinase (RTK), namely c-erbB2 (HER2/neu, ERBB2), c-fms (CSF1R), c-met (MET) and c-kit (KIT) (64-67), as well as for transcription factors that have been implicated in trophoblast invasion such as c-fos (FOS) and c-jun (JUN), in addition to c-myc (MYC) and c-ets1 (ETS) (68)(69)(70)(71). Additionally, in iEVT, c-sis (SIS, Platelet-derived Growth Factor Beta (PDGFB)) is expressed, which encodes for one of the two chains (the B-chains) constituting Platelet-derived Growth Factor (PDGF) (72) and in EVT the c-ras family (Kirsten rat Sarcoma viral oncogene (K-RAS), Neuroblastoma RAS viral oncogene homolog (N-RAS), and Harvey rat sarcoma (H-RAS)) is expressed encoding for Rat sarcoma (RAS) proteins that regulate cellular proliferation and inflammation in the human placenta (73,74). All the aforementioned proto-oncogenes are crucial in the first step of malignant transformation and its physiological expression occurs during the first week of pregnancy promoting proliferation, migration, and invasion of the trophoblast (2).…”
Section: Similarities and Differences Between Cancer Cells And Trophomentioning
confidence: 99%